TAVARES RIBEIRO,María Manuela (coord.): Mare Oceanus Atlantico:espaço de diálogos. Coimbra: Almedina, 2007. - Pando Ballesteros, María de la Paz (Studia Historica. Historia Contemporánea, 2011)
Reseña